How Can the Embodiment of Women Leadership Alter the Stereotypically Masculine Schema for Leadership? - Anh, Hoang Thi Lan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 5E, 2019)
Nowadays, the perception of leadership is different from the traditional one that used to align to agentic characteristics. However, from the top of mind, people normally think about masculine characteristics when referring to the concept of leadership. This can be so disadvantageous for female leaders in that they can be trapped in the line between two perspectives: one of their natural characteristics and one that is suitable for stereotypical definitions of leadership. By in-depth interview with nine women in top management positions in (partly) private sectors in Vietnam, the study aims to explore how the embodiment of female leadership can change the stereotypically masculine schema for leadership. An emerging finding is that women do not try to manifest their appearance and competency as recommended in theory. Instead, they embody their leadership by bringing happiness to others, by helping others to achieve high results and making others satisfied in their life and work. More importantly, they build up their followership with sincere hearts, which is relevant to the female instincts of caring, and nurturing and with their natural skills and warm hearts. Accordingly, this leads to a recommendation that women in leadership should not blur their natural characteristics. Instead, they should consider their distinctive strengths for their further development.